The secret life of wader chicks : understanding the ontogeny of behaviours towards independence in Eurasian oystercatchers (Haematopus ostralegus) - Bobeková, Ingrid, 1991- (2022)
Wader populations across the world are declining largely due to direct and indirect anthropogenic impacts on the quality of coastal and near-coastal habitats on which they rely. Iceland, an internationally important area for breeding migratory waders, has undergone large-scale landscape alterations and faces more in the future. Habitat use and requirements of juveniles might influence the ontogeny of key behaviours as they mature, and consequently their recruitment probability. However, the links between behaviours displayed at early life stages and environmental conditions experienced during those stages are still not well understood. This thesis addresses this knowledge gap and explores the ontogeny and variation in habitat use and behaviour of Eurasian oystercatcher (Haematopus ostralegus) chicks. This study was carried out during the 2020 breeding season, in a population breeding in the Westfjords, NW Iceland. Chick behaviours in 15 colour-ringed families were recorded every minute during 1-hour sessions for up to 14 weeks. The level of interactions chicks had with their parents (defined as following-feeding behaviour) varied significantly in relation to the tidal state and hatching period, with chicks interacting more with their parents during low tide and if they hatched later in the season. However, the level of interactions did not differ across families, age, brood size, or habitat type. The proportion of coastal and terrestrial habitats used by chicks varied across families, age, and tidal state, and the main behaviours observed were dependent on the habitat occupied by the chicks during the session. This study contributes to the understanding of the links between habitat use and chick’s behaviour and discusses the potential impacts towards independence. Vaðfuglastofnar um allan heim eru á niðurleið að stórum hluta vegna beinna og óbeinna mannvistarlegra áhrifa á gæði búsvæða, sem þeir eru háðir, á ströndinni og í nálgæð við strendurnar. Ísland er alþjóðlega mikilvægt svæði fyrir vaðfugla, sem verpa ...